Menggali Motivasi Siswa di Biologi Menggunakan Pembelajaran Diferensiasi Terintegrasi Model Pembelajaran Berbasis Masalah - Suhardi, Rizal M.; ,, Karmilawati; Admawati, Harsi; Mutia, Nur Balqis; Faresta, Rangga Alif (Biota, 2023)
The purpose of this study was to explore senior high school students’ motivation in biology class using differentiated instruction integrated with the problem-based learning (PBL) model. The metabolism system was used as the topic in the learning process. Thirty 12th-grade senior high school students in East Lombok were employed as subjects. The data were collected in the posttest using a learning motivation questionnaire. It consists of six learning motivation indicators. Descriptive statistics analysis by determining the mean value and standard deviation using R Studio was used to analyze the data. The result showed students’ motivation in the biology class using differentiated instruction integrated with a PBL model was categorized as good. The findings of this study can be used as considerations of differentiated instruction integrated with PBL model implementation to enhance students' motivation based on different characteristics of students in the class.